2018
DOI: 10.1055/s-0039-1678749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deployment on Reproductive Health in U.S. Active-Duty Servicewomen and Veterans

Abstract: Reproductive-age women are a fast-growing component of active-duty military personnel who experience deployment and combat more frequently than previous service-era women Veterans. With the expansion of the number of women and their roles, the United States Departments of Defense and Veterans Affairs have prioritized development and integration of reproductive services into their health systems. Thus, understanding associations between deployments or combat exposures and short- or long-term adverse reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…There have also been changes in recent years to military guidelines on healthcare and contraception. The Veterans Access, Choice, and Accountability Act of 2014 expanded healthcare options for veterans with specific “burden[s]” to receive healthcare with “choice” contracted providers [ 58 ]. Specific branches of the military have also introduced new policies impacting the availability of contraception for service members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been changes in recent years to military guidelines on healthcare and contraception. The Veterans Access, Choice, and Accountability Act of 2014 expanded healthcare options for veterans with specific “burden[s]” to receive healthcare with “choice” contracted providers [ 58 ]. Specific branches of the military have also introduced new policies impacting the availability of contraception for service members.…”
Section: Resultsmentioning
confidence: 99%
“…Several policy changes have also increased contraceptive appropriateness for military members and veterans. The VA Mission Act of 2018 increased the appropriateness of care by providing continuing education for community providers who serve veterans [ 58 ]. Similarly, in 2019, the Defense Health Agency [ 84 ] established procedures for comprehensive contraceptive counseling with Military Health System beneficiaries through the policy entitled Comprehensive Contraceptive Counseling and Access to the Full Range of Methods of Contraception.…”
Section: Resultsmentioning
confidence: 99%
“…The Veterans Access, Choice, and Accountability Act of 2014 expanded healthcare options for veterans with specific burdens by allowing them to receive healthcare with choice contracted providers (Gawron et al, 2018). Studies exploring the impact of this Act showed that it increased provider education and patient healthcare access, including reproductive healthcare access, especially in rural areas (Albanese, 2018;Hussey et al, 2016;Mattocks et al, 2017;Stroupe et al, 2019).…”
Section: Veterans Access Choice and Accountability Actmentioning
confidence: 99%